2022
DOI: 10.1002/ejoc.202200330
|View full text |Cite
|
Sign up to set email alerts
|

Radical Deoxyfunctionalisation Strategies**

Abstract: Due to their abundance and readily available synthesis, alcohols provide ideal handles for the selective derivatisation of organic molecules. Radical chemistry offers versatile strategies for the conversion of Csp3−O bonds into a wide range of Csp3−C, Csp3−H, or Csp3−heteroatom bonds. In these reactions, alcohols are readily derivatised with an activator group which can undergo facile mesolysis to generate a primary, secondary, or tertiary open‐shell species that can engage in further transformations. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…Actinometric quantum yield measurements (Φ = 90) speak in favor of a radical chain process, with persulfate anion acting as chain carrier (Scheme 10B). 71 Overman and coworkers reported a conceptually related double decarboxylative Minisci reaction of heteroarenes (10.1) with alkyl oxalates (10.7) 72 (Scheme 10C). 70 [Ir-1], in combination with (NH 4 ) 2 S 2 O 8 as terminal oxidant, could generate densely substituted tertiary radicals from the corresponding oxalates (E 1/2 ox = −1.22 V vs SCE) via reductive quenching.…”
Section: Late-stage Aromatic C(sp 2 )−H Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinometric quantum yield measurements (Φ = 90) speak in favor of a radical chain process, with persulfate anion acting as chain carrier (Scheme 10B). 71 Overman and coworkers reported a conceptually related double decarboxylative Minisci reaction of heteroarenes (10.1) with alkyl oxalates (10.7) 72 (Scheme 10C). 70 [Ir-1], in combination with (NH 4 ) 2 S 2 O 8 as terminal oxidant, could generate densely substituted tertiary radicals from the corresponding oxalates (E 1/2 ox = −1.22 V vs SCE) via reductive quenching.…”
Section: Late-stage Aromatic C(sp 2 )−H Functionalizationmentioning
confidence: 99%
“…Actinometric quantum yield measurements (Φ = 90) speak in favor of a radical chain process, with persulfate anion acting as chain carrier (Scheme B) . Overman and co-workers reported a conceptually related double decarboxylative Minisci reaction of heteroarenes ( 10.1 ) with alkyl oxalates ( 10.7 ) (Scheme C) …”
Section: Late-stage Aromatic C(sp2)–h Functionalizationmentioning
confidence: 99%
“… [16] While Barton‐McCombie variants designed to reduce or eliminate trialkyl tin reagents have been developed, these approaches remain limited in scope and still require unstable thiocarbonyl activating groups, which can also be difficult to install. As a result, the development of alternative deoxygenation methods continues to be an area of considerable synthetic interest [17–37] . Specifically, mechanistically distinct polar S N 1 and S N 2‐type substitution processes that exploit silane hydride sources are increasingly favored alternatives [38–40] .…”
Section: Introductionmentioning
confidence: 99%
“…Within the past decade, the development of visible-light photoredox chemistry provides a preeminent handle for deoxygenative radical functionalization of alcohols. Numerous photoredox catalytic methods have emerged to activate alcohols for homolytic cleavage of C­(sp 3 )–O bonds . However, the developed approaches are either not amenable to primary alcohols for generation of nonstabilized alkyl radicals or require noble metal photocatalysts .…”
mentioning
confidence: 99%
“…Numerous photoredox catalytic methods have emerged to activate alcohols for homolytic cleavage of C­(sp 3 )–O bonds . However, the developed approaches are either not amenable to primary alcohols for generation of nonstabilized alkyl radicals or require noble metal photocatalysts . Very recently, we revealed that a xanthate anion can be directly excited by visible light and exhibits strong reducing ability in its excited state (* E 1/2 red < −2.4 V vs SCE) .…”
mentioning
confidence: 99%